2020
DOI: 10.3390/ph13110398
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Enzyme l-Lysine α-Oxidase Affects the Amino Acid Metabolism in the Brain and Decreases the Polyamine Level

Abstract: The fungal glycoprotein l-lysine α-oxidase (LO) catalyzes the oxidative deamination of l-lysine (l-lys). LO may be internalized in the intestine and shows antitumor, antibacterial, and antiviral effects in vivo. The main mechanisms of its effects have been shown to be depletion of the essential amino acid l-lys and action of reactive oxidative species produced by the reaction. Here, we report that LO penetrates into the brain and is retained there for up to 48 h after intravenous injection, which might be expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The enzyme LO exhibits high antitumor activity due to the higher elevation of L-lysine in tumor tissue compared to normal tissue [ 4 , 7 ]. L-Lysine is an essential amino acid present in body tissue and blood plasma, which plays an important functional role in metabolism [ 8 ]. Therefore, deprivation of L-lysine is an important issue caused by LO administration to animals.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme LO exhibits high antitumor activity due to the higher elevation of L-lysine in tumor tissue compared to normal tissue [ 4 , 7 ]. L-Lysine is an essential amino acid present in body tissue and blood plasma, which plays an important functional role in metabolism [ 8 ]. Therefore, deprivation of L-lysine is an important issue caused by LO administration to animals.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylation and deacetylation of proteins, particularly histones and non-histone proteins, have also been linked to the pathogenesis of PD [ 149 ]. Some studies suggest that the serum level of another amino acid, lysine, is linked to these regulatory processes by influencing the function of the relevant enzymes [ 150 ]. However, its deficiency may lead to impaired metabolic processes responsible for the regulation of mood and memory [ 149 ].…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…PA are essential in the anti‐inflammatory and preventive role of LACC1 against bacterial infection, study has found that PA can control the differentiation of T helper cells by regulating the synthesis of enzymes and amino acids (Puleston et al, 2021) and another study also found that PA metabolism in microbes regulates macrophage differentiation (Nakamura et al, 2021). Elena et al reported that PA are responsible for regulating many processes, including cell proliferation, and that depletion of l ‐ORN, a precursor of PA, leads to a significant and long‐term decrease in PA concentrations (Lukasheva et al, 2020). As we know, after activation, macrophages can be divided into M1 and M2 subtypes, with M1 macrophages mainly involved in promoting inflammatory responses and M2 macrophages mainly involved in anti‐inflammatory responses.…”
Section: Figurementioning
confidence: 99%
“…Cell ell B Biology iology I International nternationalreported that PA are responsible for regulating many processes, including cell proliferation, and that depletion of L-ORN, a precursor of PA, leads to a significant and long-term decrease in PA concentrations(Lukasheva et al, 2020). As we know, after activation, macrophages can be divided into M1 and M2 subtypes, with M1 macrophages mainly involved in promoting inflammatory responses and M2 macrophages mainly involved in anti-inflammatory responses.…”
mentioning
confidence: 99%